352Postpartum diet quality: A cross‐sectional analysis from the Australian longitudinal study on women's health. (2nd September 2021) - Martin, Julie; Joham, Anju; Mishra, Gita; Hodge, Allison; Moran, Lisa; Harrison, Cheryce
Abstract: Background: Reproductive‐aged women are at high risk of developing obesity, and diet quality is a potential modifiable risk factor. There is limited research exploring postpartum diet quality. Methods: Using data from the Australian Longitudinal Study on women's Health of women, who reported having previously given birth, we investigated the association between time since childbirth and diet quality, and differences in energy, macronutrients, micronutrient intake, and diet quality assessed by the dietary guideline index (DGI) in women stratified by time from last childbirth, early (≤6 months; n = 558) and late (7–12 months; n = 547), and others (>12 months post childbirth; n = 3434). Results: From this cohort, 4539 participants completed a food frequency questionnaire and were included in this analysis. Overall, diet quality was higher in early and late postpartum women (mean DGI score 89.8±10.5 and 90.0±10.2, respectively) compared to others (>12 months post childbirth), (85.2±11.7; p < 0.001). Factors positively associated with diet quality included higher education, physical activity, health provider support, and vitamin and/or mineral supplement use. Conversely, increasing time from childbirth (>12 months), smoking compared with non‐smoking and medium income level compared with no income was negatively associated with diet quality. Conclusions: A lower diet quality in women >12 months post childbirth may be reflective of increased pressures, balancing childrearing and return to work responsibilities. This highlights the need to support women beyond the postpartum period to improve modifiable factors associated with weight gain, including diet quality, to optimize health and reduce chronic disease risk. Key messages: Diet quality; nutrition; obesity; prevention; postpartum; reproductive; women